철 결핍성 빈혈 환자에서 특발망막전막 제거 도중 발생한 대량 망막출혈 - 왕리령(Li Lyung Wang); 양지호(Ji Ho Yang); 김도균(Do Gyun Kim) (Daihan angwa haghoi jabji, 2021)
목적: 철 결핍성 빈혈이 있는 특발망막전막 환자에서 망막전막 제거시 광범위한 망막출혈을 경험하였기에 이를 보고하고자 한다. 증례요약: 59세 여자 환자가 수개월 전부터 발생한 우안의 시력저하와 변형시를 주소로 내원하였다. 20년 전 위암으로 위아전절제술을 받아 만성 철 결핍성 빈혈이 있던 환자로 안과적 검사상 우안의 황반부 망막전막 진단하 유리체절제술을 시행하였다. 눈 속 집게를 이용하여 망막전막 제거 도중 상이측 분지망막동맥으로 추정되는 부위에서 광범위한 출혈이 발생하였고 지혈 후 별다른 합병증 없이 수술을 마무리하였다. 수술 후 2개월째 시력저하를 주소로 재내원하여 시행한 안저검사상 수술 시 발생한 출혈 부위를 기준으로 광범위한 황반부 견인막이 재발하였고, 이로 인한 시력저하로 2차 견인성 망막전막 제거 및 내경계막제거술을 시행하였다. 수술 후 현재 환자는 별다른 합병증 없이 경과 관찰 중이다. 결론: 만성 철 결핍성 빈혈 환자의 경우 정상인에 비해 망막혈관내피세포 손상 정도가 심하기 때문에 출혈 위험성이 높을 수 있다. 따라서 철 결핍성 빈혈을 앓고 있는 특발망막전막 환자의 경우 망막전막을 제거할 때 세심한 주의가 필요하다. Purpose: To report a case of massive retinal hemorrhage during epiretinal membrane (ERM) peeling in a patient with iron deficiencyanemia (IDA). Case summary: A 59-year-old female presented with gradually decreasing visual acuity and dysmorphopsia in the right eye forseveral months. She had a history of chronic IDA due to subtotal gastrectomy from gastric cancer 20 years prior. The patient wasdiagnosed as having macular ERM and underwent vitrectomy. During ERM peeling with intraocular forceps, we found a massiveretinal hemorrhage which was presumed to have originated from the superotemporal branched retinal artery. After hemostasis,the operation was completed without critical complications. However, 2 months after surgery, the patient presented with decreasedvisual acuity once again. In fundus examination, diffuse macular tractional ERM was evident in the proximity of the previousintraoperative hemorrhage site. The patient underwent tractional membrane and internal limiting membrane removalsurgery. The patient is currently undergoing follow-up without complications to date following the second surgery. Conclusions: Our case study describes a patient having experienced massive retinal hemorrhage presumably having originatedfrom a superotemporal branched retinal artery during ERM peeling. We speculate that the endothelial cells of retinal vessels aremore vulnerable than normal in patients with severe chronic IDA. KCI Citation Count: 0